2022-RA-929-ESGO Robotic surgery outcomes in a gynaecological oncology cancer centre. (20th October 2022) - Nikolopoulos, Manolis; Shinde, Aditi; Nath, Rahul; Sayasneh, Ahmad; Rajkumar, Savithri; Abdelbar, Ahmed; Mehra, Gautam
Abstract : Introduction/Background: Robotic surgery (RS) in gynaecological oncology has been shown to overcome the limitations of conventional laparoscopy, improve perioperative outcomes and reduce length of stay (LOS). RS has lower conversion rates and shorter learning curve than laparoscopic surgery (LS). The blood loss is significantly less. RS is preferred in morbidly obese women. We share our experience of introducing RS at our centre and study its impact on our clinical outcomes and service. Methodology: RS was introduced in December 2020 during COVID-19 pandemic. A second surgeon trained from September 2021. Data was collected prospectively recording indications, operating-time, blood loss, LOS and complications. Outcomes were compared with the Hospital Episode Statistics (HES) data and cost analysed. Results: Until May 2022, 143 cases underwent RS using da Vinci- Si, X or Xi robots. Most women (84) had endometrial cancer. Complexity of surgery increased in latter half with women with BMI>40kg/m 2 (23), large fibroid uterus(22), ovarian cancer staging(12) and radical hysterectomy(3). Median docking time was eight minutes, median operating-time was 150 minutes and median blood loss was 50 mls. Average LOS was 1.8 days and median LOS 1 day(range 0–6 days). Average LOS for LS was 3 days and open abdominal surgery 8.6 days. Minor complications(11) were treated conservatively. Two patients with adhesions had bladder injury. One surgery was converted to open abdominal surgery during the early learning phase. Introduction of robotic surgery increased the minimal-access surgery (MAS) rate by 15%. The operating-time showed decreasing trend with experience while surgical productivity average number of cases per theatre list remained the same. Conclusion: There is a significant reduction in hospital stay and a clear cost benefit of robotic surgery. There is a significant increase in the MAS rates even during the early phase of learning with no increase in overall morbidity.